2009
DOI: 10.17221/140/2009-pse
|View full text |Cite
|
Sign up to set email alerts
|

Oligonucleotide microarray methodology for taxonomic and functional monitoringof microbial community composition

Abstract: Microarray analysis is a cultivation-independent, high-throughput technology that can be used for direct and simultaneous identification of microorganisms in complex environmental samples. This review summarizes current methodologies for oligonucleotide microarrays used in microbial ecology. it deals with probe design, microarray manufacturing, sample preparation and labeling, and data handling, as well as with the key features of microarray analysis such as specificity, sensitivity and quantification potentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 74 publications
1
7
0
Order By: Relevance
“…The methodological approach was based on a DNA extraction protocol efficient in recovering actinobacterial diversity (Ságová‐Marečková et al ., ) in combination with primers specific for actinobacteria (Kyselková et al ., ). The application of taxonomic microarrays is particularly useful in situations that can be replicated under different conditions or over time (Dahllof, ; Kyselková et al ., ), and here this approach was implemented to target actinobacteria in parallel to cloning‐sequencing.…”
Section: Introductionmentioning
confidence: 99%
“…The methodological approach was based on a DNA extraction protocol efficient in recovering actinobacterial diversity (Ságová‐Marečková et al ., ) in combination with primers specific for actinobacteria (Kyselková et al ., ). The application of taxonomic microarrays is particularly useful in situations that can be replicated under different conditions or over time (Dahllof, ; Kyselková et al ., ), and here this approach was implemented to target actinobacteria in parallel to cloning‐sequencing.…”
Section: Introductionmentioning
confidence: 99%
“…Macro-and microarrays have been used for studying populations of microorganisms in clinical samples (Wang et al 2002a), the human intestine (Wang et al 2002b), human sputum (Fukushima et al 2003), air filtrates (Wilson et al 2002), soil, compost or sludge (Stralis-Pavese et al 2004;Lievens et al 2005;Kyselkova et al 2009b), ectomycorrhizal fungal communities in soil (Reich et al 2009), human pathogens or other bacteria in water (Peplies et al 2004;Urakawa et al 2007), and human pathogens in milk (Giannino et al 2009). Using microarrays to study microbial populations on plant surfaces is less common, and only one example of a study of microbial populations on ready-to-eat vegetable salads could be found (Rudi et al 2002).…”
Section: Using Microarrays To Study Microbial Populationsmentioning
confidence: 99%
“…Elsewhere there is discussion on the complications of base pair mismatches and of the probe dependency of signal intensity that impact on quantification. A solution to both these complications is the use of padlock probes that only ligate to perfectly matched targets (Kyselkova et al 2009b). Absolute quantification is not possible with this technique, although it is possible to determine differences between samples, but not between individual microorganisms in one sample.…”
Section: Using Microarrays To Study Microbial Populationsmentioning
confidence: 99%
“…DNA microarrays are widely used to monitor and characterize microbial communities in environmental samples (16,19,26,31,35,38,45). Microarray technology permits simultaneous interrogation of PCR amplicons or genomic DNA across a large number of probe sequences (6,9,10,21,42).…”
mentioning
confidence: 99%
“…Correlations (R values) between family-level percent abundance in the clone libraries and mean array intensity were 0.93 (P<0.01), 0.37 (P=0.46), and 0.61 (P=0. 19) for Oxalobacteriaceae, Rhodocyclaceae, and Geobacteraceae, respectively. Array signals for Rhodocyclaceae and Geobacteraceae were not responsive when the relative abundance of these taxa in the clone libraries exceeded 15%; the reason for this lack of response is unknown.…”
mentioning
confidence: 99%